Atrio-Ventricular Septal Defect in Pregnant Women, How to Deal with it: A Case Study - Caroline D. &; Yogiarto M (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Atrio-Ventricular Septal Defect in Pregnant Women, How to Deal with it: A Case Study